It Takes Two: Public Understanding of Agricultural Science and Agricultural Scientists' Understanding of the Public - Lisa Lundy; Amanda Ruth; Ricky Telg; Tracy Irani (Journal of Applied Communications, 2006)
This study examined the beliefs agricultural scientists have about the general public's understanding of science—particularly agricultural science. Respondents—members of the Southern Association of Agricultural Scientists—reported that the public does not understand agricultural disciplines or science in general. Respondents indicated that it is their responsibility to help people understand their agricultural discipline, but indicated less responsibility for helping people understand science in general. Similarly, respondents were more willing to work with reporters and to receive media relations training if it helped people understand their agricultural discipline than if it helped people understand science in general. Respondents agreed that they would also participate in media relations training if they believed there would be a personal benefit or a benefit to their university. While respondents agreed that it is their responsibility to help people understand their agricultural discipline, they were less certain of their colleagues' conviction of this responsibility.